Image reconstruction for liquid-gas regime identification based on multiple excitation sources in electrical resistance tomography system - Yasmin, Abdul Wahab; M. F., Fuad; N. M., A. Ghani; Z. M., Zain; M. M., Noh; Mohd Anwar, Zawawi; M. S., Najib (IOP Publishing, 2019)
Electrical resistance tomography (ERT) reconstructs internal resistance images of the field from electrical measurements on the surface. The objective of this paper is to obtain the tomogram of the liquid-gas regime of ERT system by using multiple excitation sources. A linear back projection algorithm was implemented as a basic algorithm. Then, it was modified to suit the implementation of multiple excitation sources. A liquid-gas regime in the steel pipe was used as a tested medium. The analysis and performance of the image reconstructed which applies multiple excitation sources were compared with the single excitation technique. As a common strategy applied a single excitation source and produce problem especially at the center of the pipe, this paper mainly focuses on image reconstruction of multiple excitation sources. As a conclusion, 50% of the excitation source cannot produce the image as expected. Tomograms that produced by using the single excitation source were much better than the images obtained by using 50% of the excitation source.